Performance of Agri-Clinics and Agri-Business Centres Scheme in Andhra Pradesh - Pabbathi Sudhakar; Dr.G.Vijaya Bharathi, Dr.G.Vijaya Bharathi (International Journal of Scientific Research and Management (IJSRM), 2022)
The Government of India launched the Agri-Clinics and Agri-business Centres scheme in 2002 to establish agri-ventures by Agrigraduates to strengthen technology transfer, public advisory system, and job creation in rural areas. Candidates trained under the scheme are eligible for a subsidy of 36 percent in the case of the general category and 44 percent for women, SC/ST, Northeastern, and Mountain candidates. The program provides credit-linked, composite, and deferred grants with a three-year vesting period. The present study is a modest attempt to evaluate the performance of the Agri-Clinics and Agri-Business Centres scheme in Andhra Pradesh from its inception to the present day by looking at state-by-state, training institute-by-training institute, year by year, and project-by-project results. The study is based on the contemporary analysis of secondary data gathered from journals, magazines, articles, periodicals, websites, and the like. The results of the study showed that the success rate of the AC&ABC scheme was high in the states of Maharashtra, followed by Uttar Pradesh and Tamil Nadu. The top three activities where most of the Agri-Ventures were formed in Andhra Pradesh were Agri-Clinics, Dairy/Poultry/Piggary/Goatary, and Agri-Clinics and Agri-Business Centres. Based on the data, an average of 23 percent of the trained candidates under the AC&ABC scheme had established their Agri-Businesses in Andhra Pradesh. Bojja Venkata Reddy Agricultural Foundation, Nandyal, and Jagruti Foundation for Rural Development, Visakhapatnam, held more than half of the shares and performed well in training the candidates, with a larger number of agricultural companies being established by candidates who had undergone training through these two nodal training institutes.